PENGETAHUAN GIZI DAN KESEHATAN, PERILAKU HIDUP SEHAT, SERTA KARAKTERISTIK LINGKUNGAN FISIK RUMAH HUBUNGANNYA DENGAN KELUHAN KESEHATAN SOPIR ANGKOT - Arina Rizkiana; Siti Madanijah; Yekti Hartati Effendi (Food and Nutrition Society of Indonesia, 2010)
The objective of this study was to know the correlation between nutrition and health knowledge, behavior of healthy life, and physical characteristic of the house towards health sighs of public transportation driver. Design of this study was a cross sectional study. The criterions of sample were (1) driver of Kampus Dalam and Leuwiliang route; (2) man; (3) age more than 30 years old; (4) had been worked as public transportation driver more than 2 years; (5) can communicate and ready for having an interview. The amount of sample is 60 respondents. The type of data was primary and secondary data. The primary data (individual and family characteristic, nutrition and health knowledge, life style, pattern of food consumption, behavior of healthy life, physical characteristic of the house, and health sighs of the driver) was collected by structural questionnaire interview. The body weight and height data were collected by direct measurement on the study sites. The secondary data had been obtained from “Dinas Perhubungan” of Bogor District. This study showed that nutrition and health knowledge, behavior of healthy life, and physical characteristic of the house did not correlate to health sighs of the public transportation driver. The correlation was analyzed by Spearman’s correlation.